2011
DOI: 10.1371/journal.pone.0019863
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization with Recombinant HA and Mast Cell Activator C48/80 Elicits Protective Immunity against 2009 Pandemic H1N1 Influenza in Mice

Abstract: BackgroundPandemic influenza represents a major threat to global health. Vaccination is the most economic and effective strategy to control influenza pandemic. Conventional vaccine approach, despite being effective, has a number of major deficiencies including limited range of protection, total dependence on embryonated eggs for production, and time consuming for vaccine production. There is an urgent need to develop novel vaccine strategies to overcome these deficiencies.Methodology/Principal FindingsThe majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
(56 reference statements)
1
22
1
Order By: Relevance
“…26 Meng et al also showed that the immunization of mice with C48/80 plus influenza HA expressed in eukaryotic cells could induce the balanced Th1/Th2 responses, preferentially inducing Th2-biased immune responses. 11 These were consistent with our experimental results. However, different from NP, HA as surface glycoprotein is prone to variation, and is not suitable to be used as the antigen of UIV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…26 Meng et al also showed that the immunization of mice with C48/80 plus influenza HA expressed in eukaryotic cells could induce the balanced Th1/Th2 responses, preferentially inducing Th2-biased immune responses. 11 These were consistent with our experimental results. However, different from NP, HA as surface glycoprotein is prone to variation, and is not suitable to be used as the antigen of UIV.…”
Section: Discussionsupporting
confidence: 93%
“…[23][24][25] Some studies showed that mast cells might promote the adaptive immunity through the effector function or by releasing various cytokines, chemokines and growth factors. 11 Therefore, recently, people have started to study the efficacy of MC activator C48/80 as an adjuvant, and C48/80 has been shown to be a potential mucosal adjuvant. Just like other mucosal adjuvants, C48/80 as a nontoxic nasal adjuvant 12 can also induce effective sIgA at the mucosal location, and clear the virus in the early stage of pathogen invasion, playing an immunological effect.…”
Section: Discussionmentioning
confidence: 99%
“…A similar dosage of HA for three-dose i.n. immunization was reported by others, including chitosan nanoparticles (15 g HA per dose) [30,31] or co-delivery with a mast cell activator protein (9 g HA per dose) [32]. We found that the recombinant H5HA protein antigen had to be formulated in oil-in-water emulsions (i.e.…”
Section: Discussionmentioning
confidence: 72%
“…Among them are γ-PGA, α-galactosylceramide - a CD1d ligand, and Iscomatrix (colloidal, spherical structures, comprising of saponin such as Quil A, cholesterol and a phospholipid), which have been used in different vaccine studies [131, 245247]. Furthermore, a mast cell activating compound C48/80 has been shown to be a safe and effective nasal adjuvant in mice [248, 249]. Water soluble vitamin E derivative (d-α-tocopheryl polyethylene glycol 1000 succinate) is also suggested as a promising nasal vaccination potentiator [250].…”
Section: Adjuvants For Mucosal Routesmentioning
confidence: 99%